Participatory cultures and knowledge generative scenarios: rereading 3D virtual worlds - Daniela Cuccurullo (Firenze University Press, 2019)
In an Information society, the web 2.0, in its evolution towards 3.0, represents the most evident transformation of knowledge transmission from the Gutenbergian model into new forms of connective learning and shared knowledge through the global net. Networks permeate social life and daily relations, modify the forms of knowledge and give rise to new educational and training contexts, provoking osmotic flows of co-construction of knowledge. Through the presentation and analysis of some experimentation projects using 3D immersive virtual worlds in higher-education contexts, the contribution draws attention to the potential of these spaces as places of social and cultural aggregation, as socio-constructive learning environments of collective intelligence, as scenarios of participatory culture generative action.   Culture partecipative e scenari generativi della conoscenza: una rilettura degli ambienti virtuali 3D In una società informazionale il web 2.0, nella sua evoluzione verso il 3.0, rappresenta la più evidente trasformazione della trasmissione del sapere di stampo gutenberghiano in nuove forme di apprendimento connettivo e di conoscenza condivisa attraverso la rete globale. Le reti permeano la vita sociale e i rapporti quotidiani, modificano le forme della conoscenza e danno luogo a nuovi contesti educativi e formativi, provocando flussi osmotici di co-costruzione del sapere. Attraverso la presentazione e l'analisi di alcune sperimentazioni d'uso dei mondi virtuali immersivi 3D in contesti di alta formazione, il contributo focalizza l'attenzione sulle potenzialità di questi spazi come luoghi di aggregazione sociale e culturale, ambienti di apprendimento socio-costruttivo di intelligenza collettiva, scenari di azione generativa di cultura partecipativa.